Protocol for the development of a reporting guideline for clinical trials with integrated Chinese and western medicine interventions: the CONSORT extension for ICWM - Wang, Juan; Zhang, Xuan; Wang, Ping; Han, Fei; Li, Ji; Ma, Yanfang; Lyu, Aiping; Bian, Zhaoxiang (Frontiers in Medicine, 2023)
Background While Integrated Chinese and Western Medicine (ICWM) has become widely accepted as a necessary intervention for treating various diseases, key information about ICWM interventions is often missing in published clinical trials. To facilitate complete, transparent, and consistent reporting of clinical trials with ICWM interventions, an extension of the CONSORT guideline is necessary to be developed: the CONSORT-ICWM guideline. Methods The CONSORT-ICWM guideline will be developed in five stages in accordance with recommendations for the development of reporting guidelines from the EQUATOR (Enhancing the QUAlity and Transparency Of health Research) Network, including (1) project launch and registration; (2) literature review and checklist draft; (3) Delphi survey; (4) consensus meeting; and (5) finalization of the guideline. Additionally, the working group will be composed of professors with expertise in integrated medicines, traditional Chinese medicines, biomedical informatics, statistics, methodology, development of reporting guidelines, epidemiology, health economics, and paper publications. Discussion The CONSORT-ICWM guideline is to improve the reporting quality of clinical trials with ICWM interventions by ensuring the reports are complete, informative, clear, and transparent.